2015
DOI: 10.1007/s12291-015-0513-1
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I: A Molecule of Diverse Function

Abstract: Apolipoprotein A-I (apo A-I) an indispensable component and a major structural protein of high-density lipoprotein (HDL), plays a vital role in reverse cholesterol transport and cellular cholesterol homeostasis since its identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 50 publications
1
77
0
1
Order By: Relevance
“…Thus, this biomarker is a convenient and reproducible laboratory parameter. In addition to simply serving as a shuttle of cholesterol cargo during RCT, an expanded range of physiological functions of apoA1 have been described, including anti-inflammatory, anti-apoptotic, anti-parasitic, anti-bacterial, anti-viral, and anti-oxidant activities [40]. Chronic inflammation, infection, oxidative stress, and lipids have been related to tumorigenesis [41-43].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this biomarker is a convenient and reproducible laboratory parameter. In addition to simply serving as a shuttle of cholesterol cargo during RCT, an expanded range of physiological functions of apoA1 have been described, including anti-inflammatory, anti-apoptotic, anti-parasitic, anti-bacterial, anti-viral, and anti-oxidant activities [40]. Chronic inflammation, infection, oxidative stress, and lipids have been related to tumorigenesis [41-43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in cholesterol transport, other vascular beneficial effects have been attributed to apoA-I (Mangaraj et al, 2016). Recent studies have reported a potential anti-inflammatory role for apoA-I in the regulation of monocyte/macrophage recruitment to local sites of inflammation, via modulation of lipid rafts in cellular membranes which resulted in suppression of PI3K/Akt signaling (Iqbal et al, 2016).…”
Section: Apolipoprotein Mimetic Peptidesmentioning
confidence: 99%
“…AGPAT1 and AGPAT2 play roles in converting lysophosphatidic acid (LPA) into phosphatidic acid (PA) (Takeuchi and Reue 2009). APOA1, APOA4, and APOB encode key apolipoproteins to carry fats and fat-like substances in the blood (Mangaraj et al 2016;Qu et al 2019). Remarkably, we found the positive selection of one gene, ABCG5, which encodes sterolin-1 and works together with sterolin-2, encoded by gene ABCG8, to form a protein called sterolin.…”
Section: Resultsmentioning
confidence: 84%
“…MTTP is involved in the transport of triglycerides, cholesteryl esters, and phospholipids (Hussain et al 2012). APOA4 and APOB encode two key apolipoproteins responsive to carrying fats and fat-like substances in the blood (Mangaraj et al 2016;Qu et al 2019). Unlike PDA and FDA, CDA showed the lowest number of PSGs, and only three PSGs (SI, HKDC1, and ATP1B4) were detected.…”
Section: Resultsmentioning
confidence: 99%